Antarctophthirus nevelskoyi n.sp. (Anoplura: Echinophthiriidae) - a new species of parasite of the Northern fur seal (Callorhinus ursinus L., 1758) at Tyuleniy Island, Okhotsk Sea, Russia - M. Yu. Shchelkanov; E. M. Shchelkanov; T. V. Moskvina (Юг России: экология, развитие, 2021)
Aim. To perform a morphological study of seal lice (Anoplura: Echinophthiriidae) of the genus Antarctophthirus Enderlein, 1906 taken from Northern fur seals (Callorhinus ursinus L., 1758) at Tyuleniy Island, Okhotsk Sea, Russia).Material and Methods. Seal lice were collected from the nasal passages of Northern fur seal C. ursinus pups during a scheduled ecological and virological expedition to Tyuleniy Island in August 2017. Fourteen samples of seal lice (11 imago males, 1 imago female, 1 nymph of the 2nd age, 1 nymph of the 3-rd age) were stored in 70% ethanol at room temperature from the time of collection until the start of the study. Morphological features of the insects were studied using light and scanning electron microscopy and compared with the available data in the scientific literature.Results. Unique patterns of the arrangement of spines were found in the examined samples that is a sufficient species feature for representatives of this family and allows the identification of a new species of seal lice.Conclusion. A new species of seal lice, Antarctophthirus nevelskoyi n.sp., was identified and described and named after the famous Russian explorer of the Far East, Admiral Gennady Ivanovich Nevelskoy (18131876).